2015
DOI: 10.1002/smll.201500747
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Variations in Ligand Density on Cell Signaling

Abstract: Multiple simultaneous interactions between receptors and ligands dictate the extracellular and intracellular activities of cells. The concept of programmable ligand display is generally used to study the interaction between ligands, displayed on surfaces at various densities, with receptors present on cell surfaces. Various strategies are discussed here to display ligands on surfaces to study their effect on cell behavior. Only very few strategies have been reported where this display combines precise control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 72 publications
1
34
0
Order By: Relevance
“…A nonlinear correlation was observed between the density of IKVAV presented on the SLB and the number of attached AHP cells, showing a threshold of ligand density necessary for cell attachment. The effect of the ligand density on the cell behavior has also been reported in other reviews …”
Section: Multivalent Studies At Functionalized Platformssupporting
confidence: 53%
See 1 more Smart Citation
“…A nonlinear correlation was observed between the density of IKVAV presented on the SLB and the number of attached AHP cells, showing a threshold of ligand density necessary for cell attachment. The effect of the ligand density on the cell behavior has also been reported in other reviews …”
Section: Multivalent Studies At Functionalized Platformssupporting
confidence: 53%
“…However, the formation of a 3D environment, which resembles the in vivo conditions of biological interactions, can be particularly important in the study of biological systems. Cells, for examples, have shown different responses when placed in a 3D environment compared to 2D …”
Section: Methods For Controlling the Surface Densitymentioning
confidence: 99%
“…The preferred adhesion and morphological adjustment to the surface architecture is remarkable, because neither specific ligands, such as Arg‐Gly‐Asp peptides, nor biochemically modified cells are engaged in the here presented surface system. We speculate that the cell's strong preference for the SiNP surfaces is due to a combination of nanoroughness and anionic polyphosphate nature of the surface.…”
Section: Resultsmentioning
confidence: 99%
“…DNA and protein microarrays on planar surfaces are nowadays established tools in biomedical research for nucleic acid and protein profiling and they have found also their applications in cell biology. For instance, they allow one to screen for binding of cells in a multiplexed fashion, to employ different binding interactions mediated by, for example, different antibodies or cell matrix compounds which bind to different targets on a cell surface, as it is necessary to mimic stem cell niches, or to present gradients of surface features to cells to enable combinatorial testing of cell‐surface interactions . While biomolecular microarrays installed on planar surfaces can be integrated into microfluidic systems by hardware solutions, e.g., based on connected reaction chambers, the direct integration of arrays of multiple different protein binders is very difficult to achieve due to their intrinsic instability.…”
Section: Introductionmentioning
confidence: 99%